A Psycholinguistic Study on the Influence of Verbal Communication Dynamics of Employees at Bali Business School - Dakhi, Epos Sister Krismon Selan (CV Wahana Publikasi, 2026)
This study examines the dynamics of verbal communication among employees at Bali Business School (BBS) from a psycholinguistic perspective. It aims to identify the factors influencing communication processes, particularly in relation to information delivery and feedback reception, and to analyze how these dynamics affect the effectiveness of workplace interactions. The study adopts a qualitative case study design involving purposively selected participants from various organizational roles. Data were collected through participant observation, in-depth interviews, and analysis of recorded interactions to ensure triangulation and contextual depth. The findings indicate that verbal communication dynamics are influenced by a combination of psychological, sociocultural, and situational factors, including mood, emotional control, perception, cultural background, work pressure, and individual communication styles. These factors shape how messages are constructed, conveyed, and interpreted in workplace interactions. The study also finds that communication effectiveness depends on employees’ ability to adapt their communication strategies, interpret contextual cues, and regulate emotions during interaction. However, communication barriers remain evident, particularly due to differences in perception and communication styles, especially in multicultural contexts. Reflective communication strategies, emotional regulation, and intercultural awareness are identified as key elements in enhancing interaction effectiveness and maintaining professional relationships. This study contributes by integrating psycholinguistic perspectives into workplace communication research and provides practical implications for developing communication training programs in training and human resource development settings.